SELF-EDUCATIONAL COMPETENCY DEVELOPING OF STUDENTS MAJORING IN ECONOMICS AND BUSINESS WHILE FOREIGN LANGUAGE LEARNING - Світлана Боднар (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
In the given article the notions «self-education» and «self-educational competency» have been analyzed. According to modern pedagogical theory and practice, there has been shown the process of formation of the future economists' self-educational competency in the process of studying a foreign language. A substantiation of the introduction of modern information technologies techniques into the process of students' self-education has been made. The methods of the intending economists' self-educational competency have been suggested.